CHOICE OF CARBON POWDERY ENVIRONMENT FOR MICROARC CARBURIZING OF METALWARE - Yury Markovich Dombrovskiy; Makar Stepanovich Stepanov (Advanced Engineering Research, 2013)
The aim of the research is the choice of the powder environment kind and dispersion used for carburizing metalware through the electric current transmission and microarc discharge forming. The laboratory unit made-up of two containers — an external one including the electroconductive environment, and an internal one where a sample with the carburized powder is placed — is used. The application of the graphite, charcoal, coal coke, and coal (anthracite) powders is investigated. It is found that the best powder environment is the coal powder which provides both speeded heating of the diffusant and a steelwork, and the carbon oxide generation which intensifies the carburizing process. The effect of the coal and coke particle size on the specific electric resistance of powder environment, and the cementation process results are studied. With the particle size reduction, the electrical resistance of coal and coke powders rises sharply that is explained by the transient resistance increase because of the growth of the interparticle contacts number. In addition, the specific electric resistance of coal is by two orders of magnitude more than that of coke, irrespective of the fraction size. For the microarc carburizing, the powder environment with the particle size within the range of 0.3–0.6 mm is preferable. The obtained results can be used for the intensification of the metalware carburizing.